Implantation of an intraocular lens with a wavefront formation mechanism in the surgical treatment of cataracts in patients after penetrating keratoplasty - G.A. Fedyashev; D.A. Khvan; M.P. Ruchkin (Офтальмохирургия, 2022)
Purpose. The article presents a clinical case of cataract surgery with implantation and preoperative calculation of the AcrySof IQ Vivity intraocular lens (IOL) (Alcon, USA) in a patient who underwent penetrating keratoplasty 15 months ago. Material and methods. IOL calculation was based on the actual data of the optical biometry, keratotopographic measurements. Considering complaints, a decrease in the quality of life, ophthalmic status data, it was decided to perform a penetrating subtotal keratoplasty of the right eye, followed by remote phacoemulsification and implantation of an intraocular lens. Results. Patient reports good quality of vision at a distance and average distance; does not experience difficulties when working with computer, feels comfortable while driving at night. Conclusion. Delayed cataract surgery with IOL implantation with the wavefront formation mechanism after penetrating subtotal keratoplasty, only in cases of donor material stabilization, allows to get accurate refraction. Even despite the high probability of refractive error, this type and design features of the lens made it possible to obtain the optimal quality of vision for the patient.